Railway Transport Planning and Management - de Luca, Stefano; Di Pace, Roberta; Fiori, Chiara (IntechOpen, 2022)
Railway engineering is facing different and complex challenges due to the growing demand for travel, new technologies, and new mobility paradigms. All these issues require a clear understanding of the existing technologies, and it is crucial to identify the real opportunities that the current technological revolution may pose. As railway transportation planning processes change and pursue a multi-objective vision, diagnostic and maintenance issues are becoming even more crucial for overall system performances and alternative fuel solutions.